Season Long Pest Management Efficacy and Spray Characteristics of a Solid Set Canopy Delivery System in High Density Apples - Paul Owen-Smith; John Wise; Matthew J. Grieshop (Insects, 2019)
Solid set canopy delivery systems (SSCDS) are a novel foliar agrochemical delivery system designed as an alternative for airblast sprayers in high density fruit production. This study tested the pest management potential, coverage, and chemical deposition of an SSCDS using commercially available microsprinkler components over the course of a growing season. Spray coverage and deposition for a representative airblast sprayer and SSCDS were evaluated using water sensitive paper and tartrazine dye, respectively. Foliar sprays for pest suppression were applied through both systems, and damage assessments were taken at the midpoint and end of the growing season. SSCDS sprays demonstrated similar levels of coverage on the adaxial leaf surface as airblast sprays, but significantly lower coverage on the abaxial surface. However, mean levels of foliar chemical deposition was generally higher in the SSCDS. Evaluations found minimal arthropod and fungal damage in both airblast and SSCDS treated plots compared to untreated trees. The SSCDS was shown to be a viable alternative to the airblast, with inherent advantages such as rapid application time and improved worker safety. Furthermore, higher deposition on SSCDS treated foliage supports the hypothesis that SSCDS provide a higher droplet capture rate in the canopy, with less off-target loss and drift than airblast sprayers.